2017
DOI: 10.1056/nejmoa1606910
|View full text |Cite
|
Sign up to set email alerts
|

Tofacitinib as Induction and Maintenance Therapy for Ulcerative Colitis

Abstract: In patients with moderately to severely active ulcerative colitis, tofacitinib was more effective as induction and maintenance therapy than placebo. (Funded by Pfizer; OCTAVE Induction 1, OCTAVE Induction 2, and OCTAVE Sustain ClinicalTrials.gov numbers, NCT01465763 , NCT01458951 , and NCT01458574 , respectively.).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
1,194
3
49

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 1,362 publications
(1,272 citation statements)
references
References 24 publications
26
1,194
3
49
Order By: Relevance
“…Inflammatory bowel disease (IBD) refers to a collection of disorders manifested by inflammation of the small intestine and colon, including ulcerative colitis (UC) and CD. In patients with moderately to severely active UC, tofacitinib was found to be more effective as induction and maintenance therapy than placebo and is now approved for this disease . Curiously, efficacy in CD has been less consistent .…”
Section: A Brief Survey Of Approved and Late Phase Jakinibsmentioning
confidence: 99%
“…Inflammatory bowel disease (IBD) refers to a collection of disorders manifested by inflammation of the small intestine and colon, including ulcerative colitis (UC) and CD. In patients with moderately to severely active UC, tofacitinib was found to be more effective as induction and maintenance therapy than placebo and is now approved for this disease . Curiously, efficacy in CD has been less consistent .…”
Section: A Brief Survey Of Approved and Late Phase Jakinibsmentioning
confidence: 99%
“…Early results as a treatment for ulcerative colitis look promising, including evidence of mucosal healing. [246][247][248][249] The results in Crohn's disease have not been as robust, perhaps because of reliance on CDAI for outcome measurement and a high placebo response, but the data for maintenance of remission still seem positive. 250 251 Another JAK1 inhibitor, filgotinib, has been reported to be superior to placebo in inducing remission in patients with moderate to severe Crohn's disease.…”
Section: Resultsmentioning
confidence: 99%
“…128 The first in class tofacitinib is a non-selective JAK inhibitor (though it preferentially inhibits JAK 1 and JAK 3) that is already approved for use in rheumatoid arthritis. 129,130 The phase 3 OCTAVE studies of tofacitinib in moderate-to-severe UC confirmed its efficacy as both an induction and maintenance agent, 131 and it is currently under review by the FDA. There are other JAK inhibitors under development, most notably the JAK-1 selective filgotinib 132 and upadacitinib, 133 which have shown phase 2b efficacy in CD.…”
Section: What Is On the Horizonmentioning
confidence: 99%